Impact of myo-inositol treatment in women with polycystic ovary syndrome in assisted reproductive technologies - Philippe Merviel; Pandora James; Sarah Bouée; Mathilde Le Guillou; Camille Rince; Charlotte Nachtergaele; Véronique Kerlan (Reproductive Health, 2021)
Abstract Polycystic ovary syndrome (PCOS) is marked in 30 to 40% by insulin resistance and hyperandrogenism. Myo-inositol (MI) increases insulin sensitivity, decreases hyperandrogenism and improves the menstrual cycle. Its effect during assisted reproductive technologies (ART) has been studied by many authors. We conducted a review of the literature on the impact of MI administration in PCOS women in assisted reproductive technologies. Myo-inositol is effective in normalizing ovarian function, improving oocyte and embryo quality in PCOS, however further evaluations by large multicentre randomized controlled trials are needed to assess the clinical pregnancy and live birth rates in ART.